2007
DOI: 10.1007/s00253-007-1165-8
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic reduction of azo and indigoid compounds

Abstract: A customer- and environment-friendly method for the decolorization azo dyes was developed. Azoreductases could be used both to bleach hair dyed with azo dyes and to reduce dyes in vat dyeing of textiles. A new reduced nicotinamide adenine dinucleotide-dependent azoreductase of Bacillus cereus, which showed high potential for reduction of these dyes, was purified using a combination of ammonium sulfate precipitation and chromatography and had a molecular mass of 21.5 kDa. The optimum pH of the azoreductase depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The intestinal microflora metabolizes ingested azo dyes to colorless aromatic amines, using NAD(P)H-dependent azoreductases [11][12][13][14]. Although the dyes can be reduced in the mammalian liver to form aromatic amines, the intestinal microflora is probably primarily responsible for the in vivo reduction of azo dyes [10][11][12][13][14]. Chequer et al [15] demonstrated the mutagenicity of DO1 using the micronucleus assay in human lymphocytes and in the HepG2 human liver cell line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal microflora metabolizes ingested azo dyes to colorless aromatic amines, using NAD(P)H-dependent azoreductases [11][12][13][14]. Although the dyes can be reduced in the mammalian liver to form aromatic amines, the intestinal microflora is probably primarily responsible for the in vivo reduction of azo dyes [10][11][12][13][14]. Chequer et al [15] demonstrated the mutagenicity of DO1 using the micronucleus assay in human lymphocytes and in the HepG2 human liver cell line.…”
Section: Introductionmentioning
confidence: 99%
“…The human intestinal microbiota plays a role in the degradation of azo dyes, with azo reduction being the most important reaction with respect to their toxicity and mutagenicity [10]. The intestinal microflora metabolizes ingested azo dyes to colorless aromatic amines, using NAD(P)H-dependent azoreductases [11][12][13][14]. Although the dyes can be reduced in the mammalian liver to form aromatic amines, the intestinal microflora is probably primarily responsible for the in vivo reduction of azo dyes [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…17 They can be metabolized by azoreductase enzymes at the gastrointestinal cells, producing free aromatic amines that are potentially carcinogenic and mutagenic. 13,[18][19][20] Several studies have indicated that azo dyes can cause DNA damage. 4,[21][22][23][24] DNA plays a key role in cell proliferation, synthesis of proteins, and transcription of genetic information in living cells.…”
Section: 2mentioning
confidence: 99%
“…13,[18][19][20] Several studies have indicated that azo dyes can cause DNA damage. 4,[21][22][23][24] DNA plays a key role in cell proliferation, synthesis of proteins, and transcription of genetic information in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ammoniumazo-1 (Am-Azo-1), citrus yellow, orange G, Ponceau BS, and ruby red were inert to reduction with BTI10 (pHs 5.5 to 8.3). A lack of reduction of the last two is surprising because they have been reduced by other azoreductases (2,3,8,9). At pH 6, BTI10 efficiently reduced MeO, o-methyl red (o-MeR), and BHQ-10 but flame orange (FO) and Janus green B (JGB) only poorly.…”
mentioning
confidence: 99%